2017
DOI: 10.5194/amt-2017-314
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information content of OCO-2 oxygen A-band channels for retrieving marine liquid cloud properties

Abstract: Abstract. An information content analysis is used to select channels for a marine liquid cloud retrieval using the high-spectralresolution oxygen A-band instrument on NASA's Orbiting Carbon Observatory-2 (OCO-2). Desired retrieval properties are cloud optical depth, cloud pressure thickness and cloud-top pressure and the optimal channels depend on the atmospheric state, cloud properties and position within the OCO-2 swath. Based on information content criteria we select a micro-window of 75 10 of the 853 funct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In particular, for deviations of 50 % in the cloud geometrical thickness, the retrieval errors in the cloud top height and cloud optical thickness are lower than 0.4 and 2.0 km respectively. Note that for the accurate retrieval of cloud geometrical thickness from the O 2 A-band either multi-angular (Merlin et al, 2016) or high-spectral-resolution (Richardson and Stephens, 2017) measurements are needed.…”
Section: Error Characterisationmentioning
confidence: 99%
“…In particular, for deviations of 50 % in the cloud geometrical thickness, the retrieval errors in the cloud top height and cloud optical thickness are lower than 0.4 and 2.0 km respectively. Note that for the accurate retrieval of cloud geometrical thickness from the O 2 A-band either multi-angular (Merlin et al, 2016) or high-spectral-resolution (Richardson and Stephens, 2017) measurements are needed.…”
Section: Error Characterisationmentioning
confidence: 99%
“…Several cloud retrieval algorithms based on measurements in and around the O 2 A-band at 760 nm have been developed for the GOME type of sensors: these include the ICFA (Initial Cloud Fitting Algorithm; Kuze and Chance, 1994), FRESCO (Fast REtrieval Scheme for Clouds from the Oxygen Aband; Koelemeijer et al, 2001;Wang et al, 2008), SACURA (Semi-Analytical CloUd Retrieval Algorithm; Rozanov and Kokhanovsky, 2004), UV/NIR (Diedenhoven et al, 2007), and ROCINN algorithms. These are all based on the independent pixel approximation (IPA), which is the assumption that the "radiative properties of a single satellite "pixel" are considered in isolation from neighbouring pixels" (definition of the American Meteorological Society).…”
Section: Heritage Algorithmsmentioning
confidence: 99%
“…The CRB approach works best with large pixels (Kokhanovsky et al, 2007), such as those from GOME (footprint: 320 × 40 km 2 ), where different types of clouds are combined, and errors in the cloud model are usually self-compensating. Furthermore CAL is more accurate than CRB for optically thin clouds (Rozanov and Kokhanovsky, 2004), and these kinds of clouds are the most frequent on a global scale. Previous studies using TOMS and GOME/SCIAMACHY measurements have demonstrated that a plane-parallel scattering cloud model is superior to a Lambertian reflectance cloud model for trace gas retrievals: Ahmad et al (2004) and Diedenhoven et al (2007) respectively.…”
Section: Overview Of the Cloud Retrieval Algorithmsmentioning
confidence: 99%
“…Several cloud retrieval algorithms based on measurements in and around the O 2 A-band at 760 nm have been developed for the GOME type of sensors: these include the ICFA (Initial Cloud Fitting Algorithm; Kuze and Chance, 1994), FRESCO (Fast REtrieval Scheme for Clouds from the Oxygen Aband; Koelemeijer et al, 2001;Wang et al, 2008), SACURA (Semi-Analytical CloUd Retrieval Algorithm; Rozanov and Kokhanovsky, 2004), UV/NIR (Diedenhoven et al, 2007), and ROCINN algorithms. These are all based on the independent pixel approximation (IPA), which is the assumption that the "radiative properties of a single satellite "pixel" are considered in isolation from neighbouring pixels" (definition of the American Meteorological Society).…”
Section: Heritage Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation